Kidney transplantation in children and adolescents with C3 glomerulopathy or immune complex membranoproliferative glomerulonephritis: a real-world study within the CERTAIN research network - Patry, Christian; Webb, Nicholas J. A.; Feißt, Manuel; Krupka, Kai; Becker, Jan; Bald, Martin; Antoniello, Benedetta; Bilge, Ilmay; Gulhan, Bora; Hogan, Julien; Kanzelmeyer, Nele; Ozkaya, Ozan; et al. (Pediatric nephrology, 2024)
Complement 3 glomerulopathy (C3G) and immune complex membranoproliferative glomerulonephritis (IC-MPGN) are ultra-rare chronic kidney diseases with an overall poor prognosis, with approximately 40-50% of patients progressing to kidney failure within 10 years of diagnosis. C3G is characterized by a high rate of disease recurrence in the transplanted kidney. However, there is a lack of published data on clinical outcomes in the pediatric population following transplantation.